Reproductive activity in sheep with different lambing period treated with melatonin in April - Joze Staric; Luisa Pulinas; Maria Veronica Di Stefano; Maria Consuelo Mura; Sebastiano Luridiana; Pier Paolo Bini; Vincenzo Carcangiu (Journal of Central European Agriculture, 2019)
The object was to evaluate the effect of melatonin treatment on the advance in April of the reproductive resumption in Sarda breed sheep with different lambing period. For the research two farms, located in North Sardinia between 39° and 40° N, were chosen. In each farm, 120 lactating ewes were selected: 30 lambed between October 20th and November 20th (group 1); 30 lambed between December 1st and 30th (group 2); 30 lambed between January 1st and 30th; 30 lambed between February 1st and 28th (group 4). In each farm, each group of 30 animals was divided into two subgroups of 15 animals (M and C). On April 1st, in each farm, the animals of the M subgroups were treated with a implant containing 18 mg melatonin. The subgroups C were kept as control. The lambing dates and the number of newborn lambs were recorded until 220 days after ram introduction. In treated animals greatest fertility (P<0.01) and lowest distance in days from male introduction to lambing (P<0.01) were recorded. The best reproductive performances were found in the group 1 and 2 compared to the other two groups (P<0.01). The present research shows that melatonin treatment should be made 3 or 4 months after lambing, in order to obtain optimal results.